The role of primary and secondary packaging on the antibacterial activity of sunlight exposed synthetic and herbal eye drops - Lamisha, Fariha Zerin (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.